Antibacterial Activities and Synergistic Effect of the Bioactive Compounds of Selected Medicinal Plants Against Diarrhoea-Causing Pathogens - Saadu, Murtala; Adabara, Nasiru Usman; Kuta, Faruk Abubakar; Muhammed, Hadiza Lami; Wuna, Mohamed (Asian Journal of Science, Technology, Engineering, and Art, 2023)
In this study, the antimicrobial properties and toxicological effects of Anogeissus leiocarpus and Khaya senegalensis, two traditional medicinal plants from West Africa, were investigated against diarrhea-causing pathogens. Cold maceration was used to prepare extracts from the plants. Anogeissus leiocarpus yielded 22.87g of extract, while Khaya senegalensis yielded 13.94g. Both plant crude extracts exhibited varying degrees of antibacterial activity against Vibrio cholerae, Klebsiella pneumoniae, and Salmonella enterica serovar at different concentrations. A. leiocarpus and K. senegalensis showed the highest antibacterial activity, with significantly higher zones of inhibition at all concentrations against all test organisms. The Minimum Inhibitory Concentration (MIC) for A. leiocarpus ranged from 0.10 to 0.96 mg/mL, while the Minimum Bactericidal Concentration (MBC) ranged from 0.10 to 1.09 mg/mL. For K. senegalensis, MIC ranged from 0.96 to 1.80 mg/mL, and MBC ranged from 1.02 to 1.92 mg/mL. Fractionation of the most active crude extracts resulted in the highest yields in the n-Hexane fractions for both A. leiocarpus and K. senegalensis. Significant differences were observed in the antibacterial activity of these fractions. K. senegalensis fractions and A. leiocarpus n-Hexane fraction showed the highest activity against V. cholerae, while the ethyl acetate fraction of K. senegalensis exhibited significant activity against K. pneumoniae. The aqueous fraction of A. leiocarpus displayed the highest activity against Salmonella, whereas none of the K. senegalensis fractions were active against Salmonella. Antibacterial activity of K. senegalensis ethyl acetate and A. leiocarpus n-Hexane and aqueous column chromatography fractions against the test organisms was concentration-dependent, with the highest antimicrobial activity observed at 200 mg/mL concentration. Importantly, there were no significant differences in the body weights of experimental animals across all groups. In conclusion, A. leiocarpus and K. senegalensis extracts and their fractions demonstrated promising antimicrobial properties against diarrhea-causing pathogens. These findings support their traditional medicinal use in West Africa and suggest their potential as natural remedies for combating bacterial infections.